Diversity of benthic diatoms in six main rivers of Thailand - Leelahakriengkrai P. (2014)
The diversity of benthic diatoms in six main rivers of Thailand during three seasons, were investigated in the months of March 2008, August 2008 and January 2009. Samples were collected from 6 regions in Thailand: Ping River (northern regions), Tha Chin River (central regions), Chi River (northeast regions), Chanthaburi River (eastern regions), Kwai River (western regions) and Tapee River (southern regions). Samples were taken from the upper, middle and lower parts of each river. A total of 214 of benthic diatoms were found and classified into 3 classes, 6 subclasses, 13 orders, 28 families and 50 genera. Of these, 41 taxa were recorded for the first time in Thailand. The most abundant species found in the main rivers of Thailand were Achnanthidium minutissimum, Cyclotella pseudostelligera, Gomphonema lagenula, Navicula cryptocephala, N. symmetrica and Nitzschia palea. © 2011 Friends Science Publishers.